A force and moment compensation method for a hardware-in-the-loop docking simulator based on the stiffness identification of the docking mechanism. (June 2021) - Hu, Yan; Gao, Feng; Qi, Chenkun; Zhao, Xianchao; Wang, Qian
Highlights: A high fidelity simulation of a hardware-in-the-loop docking simulator is achieved. Factors that lead to divergence and distortion are thoroughly analyzed. A force and moment compensation method is proposed. The stiffness of the docking mechanism is a key parameter. A stiffness identification model is deduced. Abstract: A hardware-in-the-loop (HIL) docking simulator is an important validation facility on the ground for space docking. To reproduce the space docking process, the HIL docking simulator needs to solve the simulation distortion problem. In this paper, a force and moment compensation approach is presented to achieve a high-fidelity HIL simulation for a six degree-of-freedom docking simulator. The whole loop in the HIL simulation is thoroughly analyzed, and the sources that lead to the distortion are illustrated. The force and moment compensation method considers the distortion sources from the time lag of the force sensor, the motion lag of the motion simulator and especially the deformation of the simulator mechanical structure. One key step in the force and moment compensation is the stiffness identification of the docking mechanism. The stiffness relationship among the whole system stiffness, the stiffness of the docking mechanism, and the structural stiffness of the simulator, is established. A stiffness identification model is deduced to obtain the stiffness of the docking mechanism from the whole system stiffness by excluding the structural stiffness of the simulator in real-time. The experimental results show the proposed compensation method can achieve a high-fidelity simulation for the docking simulator.